Pengaruh Profesionalisme Auditor dan Teknik Audit Investigatif dalam Pengungkapan Fraud - Sindy Septiani; Arinda Dwi Cahyani; Nera Marinda Machdar (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research begins the role of professionalism of investigative auditors and investigative audit techniques in detecting fraud in Indonesia. The increase in cases of poverty encourages understanding of the influence of these variables in detecting and revealing the level of conditions. The application of optimal audit techniques and standards, together with high auditor professionalism, is expected to result in maximum detection and disclosure of conditions. This qualitative literature study analyzes previous articles and research. Data was collected from relevant journals, books and internet articles. The results show that auditor professionalism and investigative audit techniques reveal conditions and determine the level of conditions.